1966
DOI: 10.1021/bi00874a039
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Metabolism of Blood-Borne Cholesterol Sulfate*

Abstract: Using isotopic dilution techniques, certain metabolic properties of cholesteryl 3/3-sulfate [cholesterol sulfate (CS)], a substance that has recently been isolated from human blood and adrenal tissue, were studied in two normal human subjects. Thus, the concentration (c) of circulating CS" in the plasma was found to be 328 and 924 jug/100 ml. Following the injection of [14C]CS, the metabolic clearance rate (MCR) of this compound was determined from the disappearance curve of the tracer from plasma. From these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1970
1970
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…The apparent validity of this initial value was soon confirmed by reports of plasma cholesterol sulfate levels involving a limited number of subjects that ranged from 174 to 328 g/100 ml (31)(32)(33). Studies involving larger groups of subjects but utilizing different methodologies revealed plasma cholesterol sulfate levels in normal subjects of 150-250 g/ml (34,35), 178 Ϯ 31 g/100 ml (men and women) (36), 134-322 g/ml (men) and 117-214 g/ ml (women) (37), 118-138 g/ml (men) (38), 272 Ϯ 64 g/ml (men) and 175 Ϯ 70 g/ml (women) (39), 134 Ϯ 29 g/ml (men) (40), and 253 Ϯ 25 g/ml (women) (41).…”
Section: Plasma Levelsmentioning
confidence: 89%
See 2 more Smart Citations
“…The apparent validity of this initial value was soon confirmed by reports of plasma cholesterol sulfate levels involving a limited number of subjects that ranged from 174 to 328 g/100 ml (31)(32)(33). Studies involving larger groups of subjects but utilizing different methodologies revealed plasma cholesterol sulfate levels in normal subjects of 150-250 g/ml (34,35), 178 Ϯ 31 g/100 ml (men and women) (36), 134-322 g/ml (men) and 117-214 g/ ml (women) (37), 118-138 g/ml (men) (38), 272 Ϯ 64 g/ml (men) and 175 Ϯ 70 g/ml (women) (39), 134 Ϯ 29 g/ml (men) (40), and 253 Ϯ 25 g/ml (women) (41).…”
Section: Plasma Levelsmentioning
confidence: 89%
“…Production rates (PRs) of cholesterol sulfate have not been evaluated extensively, but, based on estimated metabolic clearance rates (MCRs) and plasma steroid/sterol concentrations ([S]), PRs (PR ϭ MCR ϫ [S]) of 35 mg/ day and 163 mg/day were determined for two normal subjects (31). Interestingly, the PR for cholesterol sulfate appears to be comparable to the PR of ‫ف‬ 45 mg/day determined for the other prominent circulating steroid sulfate, i.e., DHEA sulfate.…”
Section: Synthesis and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Several sulfonated sterols have been reported to be widely distributed in steroidogenic tissues (26) and to circulate in plasma at concentrations ranging from 328 to 924 mg/100 ml, with a blood production rate of 35-163 mg/day (27). A similar sulfonated oxysterol derivative, 24-hydroxycholeterol 3-sulfonate 24-glucuronide (based on MS/MS analysis), was reported in the serum and urine of children with severe cholestatic liver diseases (26).…”
Section: Discussionmentioning
confidence: 99%
“…The C-21-sulfate bears some analogy to the sulfurylated side chain of the bile acids. Recently, we have found (unpublished observations) that the metabolic clearance rate of plasma DOC-SO4 is quite high (650-1,000 liters/24 h) compared with that of other steroid sulfates; e.g., the metabolic clearance rate of plasma dehydroisoandrosterone sulfate (26) and cholesteryl sulfate (27) in men and nonpregnant women is only 10 liters/24 h and those of estrone sulfate (28,29), pregnenolone sulfate (30), and testosterone sulfate (31) are of the order of 150 liters/24 h. This may be due to preferential entry into bile of steroid-21-sulfates compared to steroid-3d-sulfates or steroid-17f3-sulfates or else due to bacterial metabolism of DOC-SO4 in a manner that precludes reabsorption of DOC-SO4 and thus constitutes irreversible metabolism (i.e., conversion to progesterone and metabolites thereof). It has been shown that the rate of entry of dehydroisoandrosterone sulfate into bile is slow (32).…”
Section: Discussionmentioning
confidence: 97%